2007
DOI: 10.1111/j.1365-313x.2007.03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐sensitive GFP in Arabidopsis thaliana is a quantitative biosensor for the redox potential of the cellular glutathione redox buffer

Abstract: SummaryThe cellular glutathione redox buffer is assumed to be part of signal transduction pathways transmitting environmental signals during biotic and abiotic stress, and thus is essential for regulation of metabolism and development. Ratiometric redox-sensitive GFP (roGFP) expressed in Arabidopsis thaliana reversibly responds to redox changes induced by incubation with H 2 O 2 or DTT. Kinetic analysis of these redox changes, combined with detailed characterization of roGFP2 in vitro, shows that roGFP2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
521
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(544 citation statements)
references
References 49 publications
20
521
2
1
Order By: Relevance
“…The distribution of GSH between different cellular compartments is important because it establishes and supports the redox environment in which metabolism and signalling events occur. The GSH redox potential of the cytosol of plant cells in vivo has been extensively monitored using redox-sensitive green fluorescent protein (roGFP) probes (92)(93)(94). Parallel analyses of the redox state of nucleus and cytosol using a yellow fluorescent protein-based redox sensor (rxYFP) in the yeast S. cerevisiae showed that nuclear GSH redox environment is highly reducing and similar to that of the cytosol (95), a situation that is also observed in plant cells (Figure 3; 44; 96).…”
Section: The Redox Environment Of the Cytosol And Nucleimentioning
confidence: 99%
“…The distribution of GSH between different cellular compartments is important because it establishes and supports the redox environment in which metabolism and signalling events occur. The GSH redox potential of the cytosol of plant cells in vivo has been extensively monitored using redox-sensitive green fluorescent protein (roGFP) probes (92)(93)(94). Parallel analyses of the redox state of nucleus and cytosol using a yellow fluorescent protein-based redox sensor (rxYFP) in the yeast S. cerevisiae showed that nuclear GSH redox environment is highly reducing and similar to that of the cytosol (95), a situation that is also observed in plant cells (Figure 3; 44; 96).…”
Section: The Redox Environment Of the Cytosol And Nucleimentioning
confidence: 99%
“…The roGFP2 is a redoxsensitive fluorescent probe that can exist in either reduced (dithiol, -SH HS-) or oxidized (disulfide, -SS-) forms, each with a different excitation spectrum. In vivo, the redox state of roGFP2 depends on the redox potential of glutathione (itself a function of the [GSH] 2 / [GSSG] ratio; Meyer et al, 2007), but possibly also by other molecules (e.g. ROS and RNS) that might react with roGFP2 redox-sensitive cysteines.…”
Section: Cadmium Induces Accumulation Of No and Cytosolic Oxidation Imentioning
confidence: 99%
“…The pH of the media was adjusted to 6.0 6 0.1 with 0.5 N KOH before autoclaving at 121°C for 20 min. Seeds of the transgenic roGFP2 Arabidopsis line (Meyer et al, 2007) were provided by Markus Schwarzländer. Seeds of gapc1 and gapc2 Arabidopsis transfer DNA (T-DNA) insertional mutant lines were from the SALK Institute (SALK_010839 and SALK_016539, respectively).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then researchers have taken advantage of this tool to monitor the redox state involved in glutathione metabolism (Meyer et al, 2007) or the removal of ROS by manganese superoxide dismutase in mitochondria (Morgan et al, 2008), and additional papers are anticipated. Other valuable methods for in vivo monitoring of ROS were also introduced, including autoluminescence (Havaux et al, 2006) and biophotone imaging (Kobayashi et al, 2007) as well as luciferase imaging (Shao et al, 2007).…”
Section: Advances In Ros Imagingmentioning
confidence: 99%